Development of colorimetric method for the quantification of methyl salicylate in bulk and formulations - Sajin Kattuvilakam Abbas, Suseem Sundaram Rengitham (Journal of Applied Pharmaceutical Science, 2014)
Methyl salicylate is chemically methyl-O-hydroxybenzoate and act as an active ingredient in many topical analgesic preparations. It posses good counter irritant activity. In this present study, a colorimetric method is developed for the quantitative estimation of methyl salicylate, both in the bulk form and in the formulations. A dark bluish – purple colour is formed between methyl salicylate and ferric chloride reagent. The intensity of the colour is directly related to the concentration of methyl salicylate present. The developed method was simple and gave accurate and precise results. The developed colour had its maximum value of absorbance at 537 nm when scanned in the visible region. The absorbance of the coloured system was measured at 537 nm. Beer’s law was obeyed in the range of 12 to 72 µg/mL. The equation for the straight line was found to be, y = 0.0075 x + 0.002 with correlation coefficient value of 0.996. The developed method was applied to semi – solid formulations for the quantitative estimation of methyl salicylate. The percentage of recovery was between 99.62 % in the formulation. The method proved to be a convenient analytical tool for the quantity determination of methyl salicylate.
Keywords: Methyl salicylate, Ferric chloride, colorimetry.